Hypoglycemia While Driving in Insulin-Treated Patients: Incidence and Risk Factors. Issue 8 (10th December 2021) - Lohan, Laura; Clément, Florian; Duflos, Claire; Villiet, Maxime; Castet-Nicolas, Audrey; Boegner, Catherine; Avignon, Antoine; Sultan, Ariane; Breuker, Cyril
Abstract : Supplemental digital content is available in the text. Abstract : Objectives: This study aimed to investigate a potential daily-life concern for patients with diabetes hypoglycemia while driving by (1) estimating their incidence in insulin-treated drivers, (2) determining factors associated with their occurrence, and (3) analyzing patients' behavior regarding prevention of hypoglycemia. Methods: We conducted an observational study from November 2013 to May 2018 in the endocrinology-diabetology-nutrition department of our university hospital. All patients treated for diabetes older than 18 years admitted in the department were eligible. A specific questionnaire assessing attitudes, knowledge, and consequences of hypoglycemia was provided. In this study, only insulin-treated patients who regularly drive were analyzed. Results: On the 233 insulin-treated drivers included, 45 (19%) self-reported at least 1 hypoglycemia while driving in the preceding year. Two factors were significantly associated with their occurrence: type 1 diabetes (odds ratio [OR] = 3.19; 95% confidence interval [CI] = 1.55–6.57) and experiences of asymptomatic hypoglycemia (OR = 2.20; 95% CI = 1.05–4.63). Awareness of the treatment hypoglycemia risk because of information provided by a medical specialist was also but nonsignificantly associated with hypoglycemia while driving (OR = 2.61; 95% CI = 0.86–7.92). Forty-one patients (18%) combined those 3 variables, 20 (49%) of them self-reported hypoglycemia while driving. Thirty-four percent of the patients never carried carbohydrates for hypoglycemia correction. Seventy-six percent do not monitor blood glucose level before driving. Conclusions: Our questionnaire allowed us to highlight that 19% our cohort of insulin-treated drivers declared experiencing hypoglycemia while driving. Risk factors identified and prevention data collected should help us better target patient education.